Cryopreservation process alters the expression of genes involved in pathways associated with the fertility of bull spermatozoa - Ebenezer Samuel King, John Peter; Sinha, Manish Kumar; Kumaresan, Arumugam; Nag, Pradeep; Das Gupta, Mohua; Arul Prakash, Mani; Talluri, Thirumala Rao; Datta, Tirtha Kumar (Frontiers in Genetics, 2022)
In bovines, cryopreserved semen is used for artificial insemination; however the fertility of cryopreserved semen is far lower than the fresh semen. Although cryopreservation has been shown to alter sperm phenotypic characteristics, its effect on sperm molecular health is not thoroughly understood. The present study, using Next Generation Sequencing method, investigated the effect of cryopreservation on sperm transcriptomic composition of bull spermatozoa. In freshly ejaculated bull spermatozoa, 14280 transcripts were detected; on the other hand, only 12375 transcripts were detected in cryopreserved spermatozoa. Comparative analysis found that 241 genes were up-regulated, 662 genes were down-regulated and 215 genes were found to be neutral in expression in cryopreserved spermatozoa compared to fresh spermatozoa. Gene ontology analysis indicted that dysregulated transcripts were involved in nucleic acid binding, transcription specific activity, protein kinase binding involving protein autophosphorylation, ventricular septum morphogenesis and organ development process. Moreover, the dysregulated genes in cryopreserved spermatozoa were found to involve in pathways associated with glycogen metabolism, MAPK signalling, embryonic organ morphogenesis, ectodermal placode formation and regulation of protein auto-phosphorylation. It is inferred that cryopreservation process induced alterations in the abundance of sperm transcripts associated with potential fertility associated functions and pathways, which might partly explain the reduced fertility observed with cryopreserved bull spermatozoa.